Current Research on the Immune Response to Experimental Sporotrichosis - Carlos, Iracilda Zeppone [UNESP]; Sassa, Micheli Fernanda [UNESP]; da Graca Sgarbi, Diana Bridon; Polesi Placeres, Marisa Campos [UNESP]; Geraldo Maia, Danielle Cardoso [UNESP] (Springer, 2009)
Sporotrichosis is often manifested as a chronic granulomatous infection and the monocytes/macrophages play a central role in the host defense system. Surface components of Sporothrix schenckii have been characterized and suggestions have been made as to their possible role in pathogenicity. Ergosterol peroxide, cell-wall compounds (alkali-insoluble fraction-F1 and lipid extract-LEY), and exoantigen from the yeast form of the fungus have been characterized as virulence factors, activating both innate, by cytotoxins linked to the activation of reactive oxygen and nitrogen species (H(2)O(2) and NO), and adaptive immune response to produce cytokines Th1 and Th2 profile. In this study, preliminary results have demonstrated that, in systemic sporotrichosis, TLR-4 triggers the innate immune response, activating an oxidative burst. These data represent the first report of the participation of TLR-4 in murine sporotrichosis, in the presence of lipids from the cell wall of S. schenckii. These results taken together may open new perspectives of study leading to an antifungal agent that could be used to benefit the entire population.
Keywords: Sporothrix schenckii; Systemic infection; Cytokines; Nitric oxide; Hydrogen peroxide; TLR-4; Th1/Th2 response